2022
DOI: 10.12669/pjms.38.8.5951
|View full text |Cite
|
Sign up to set email alerts
|

Factors leading to the academic failure of undergraduate medical students - Predict early to prevent

Abstract: Objectives: The main objective of the study was to explore the factors to predict academic failure before the first major assessment. Methods: An exploratory qualitative study was conducted from March 2021 to August 2021 at Riphah International University. Using the purposive sampling technique, 16 students and seven teachers were included in the study. Eight online interviews were conducted with students who were academic failures and two focus group discussions were held with eight high achievers and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…While in low achievers it was associated with fear in high achievers it acted as a driving force. 17 Examiners' attitude was mentioned by half of our study participants (5/10) as a contributory factor. Although not outrightly biased against them, they had the impression that the examiners they faced were Studies have shown that the more experienced examiners tend to be stricter while junior ones show more leniency.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While in low achievers it was associated with fear in high achievers it acted as a driving force. 17 Examiners' attitude was mentioned by half of our study participants (5/10) as a contributory factor. Although not outrightly biased against them, they had the impression that the examiners they faced were Studies have shown that the more experienced examiners tend to be stricter while junior ones show more leniency.…”
Section: Discussionmentioning
confidence: 85%
“…While in low achievers it was associated with fear in high achievers it acted as a driving force. 17 …”
Section: Discussionmentioning
confidence: 99%